A calorimetric system for charge and kinetic energy characterizations of pulsed electron beams. (April 2021) - Serebrennikov, Maksim; Adamov, Egor; Poloskov, Artem; Yu, Xiao; Egorov, Ivan
Abstract: The monitoring of the cross-sectional distribution of an electron beam plays a significant role in scientific research and applications. A sectioned calorimeter system combined with a detector of total electron beam current by Faraday cup was developed for estimating the charge and energy distribution of pulsed electron beams. The calorimeter, consisting of a collector with 61 sections and a matrix of remote thermal sensors (pyrometers), allows measuring the cross-sectional energy distribution of pulsed electron beam with an electron kinetic energy up to 700 keV, energy density within 3.6 J/cm 2, and total beam energy up to 50 J/pulse. The response of each section is separately monitored and the total current from all the collector sections is measured for beam charge calculation. The charge distribution is estimated in proportion to the total energy distribution. The system was tested with a pulsed electron beam ejected into the atmosphere (accelerating voltage 270 kV, current 140 A, 100 ns FWHM). The difference in the output between the developed system and diagnostics equipment of the accelerator is within 10%. With measured total energy of 4 J/pulse and transferred charge of 13.6 μC/pulse, an average electron kinetic energy of 115 keV was estimated, fulfills the monitoring of cross-sectional energy density and the estimation of the average electron kinetic energy. Highlights: The sectioned calorimeter combined with a detector of total electron beam current was developed for estimating the charge and energy distribution in the beam cross section. The set of recorded characteristics allows the average kinetic energy of electrons in the beam to be estimated. The calorimeter design and measurement procedure can be reproduced in a wide range of geometric and energy characteristics of the electron beam.